2021
DOI: 10.1128/aem.02593-20
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Metagenome-Assembled Genomes (MAGs) in Representing Natural Populations: Insights from Comparing MAGs against Isolate Genomes Derived from the Same Fecal Sample

Abstract: The recovery of metagenome-assembled genomes (MAGs) from metagenomic data has recently become a common task for microbial studies. The strengths and limitations of the underlying bioinformatics algorithms are well appreciated by now based on performance tests with mock datasets of known composition. However, these mock datasets do not capture the complexity and diversity often observed within natural populations, since their construction typically relies on only a single genome of a given organism. Further, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 35 publications
5
103
0
2
Order By: Relevance
“…Such approaches have been applied widely including in the assembly of pathogen genomes from clinical samples [ 2 ], bacterial genomes and gene clusters from the human gut [ 3 ], the rumen microbiome of cattle [ 4 ], and a project which assembled tens of thousands of MAGs by re-analysing over 10,000 previously collected metagenomes [ 5 ]. Nevertheless, despite these successes, some doubts remain about the reliability of MAG approaches when faced with complex populations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches have been applied widely including in the assembly of pathogen genomes from clinical samples [ 2 ], bacterial genomes and gene clusters from the human gut [ 3 ], the rumen microbiome of cattle [ 4 ], and a project which assembled tens of thousands of MAGs by re-analysing over 10,000 previously collected metagenomes [ 5 ]. Nevertheless, despite these successes, some doubts remain about the reliability of MAG approaches when faced with complex populations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While progress has been made in defining microbial species ( 21 23 ), the high genetic heterogeneity within diverse microbial communities, such as soils, convolute the boundaries of the fine-scale patterns of genetic diversity within microbial taxonomic units ( 12 ). For instance, metagenome-assembled genomes are often composed of a composite of strains forming a large population of mosaic genomes ( 24 ) that may not fully capture the diversity of the local population ( 25 ). As such, it remains difficult to study evolutionary rates within microbial communities (however, see refs.…”
mentioning
confidence: 99%
“…Aquatic MAGs average 3.1 Mb, host-associated MAGs average 3.0 Mb, and terrestrial MAGs average 3.7 Mb (Figure 1A). It is known that MAG assembly might discriminate against ribosomal RNAs, transfer RNAs, mobile element functions and genes of unknown function (23,24), and also that completeness estimations can be underestimated for streamlined genomes (25). For the 540 mOTUs with MAGs and isolate genomes (Figure 1C), we found that MAGs were estimated on average 3.7% smaller than isolate genomes (Figure S1).…”
Section: Extant Genome Size Distribution In the Environmentmentioning
confidence: 78%